2010
DOI: 10.1002/cncy.20074
|View full text |Cite
|
Sign up to set email alerts
|

Telecytopathology for immediate evaluation of fine‐needle aspiration specimens

Abstract: Nonalcoholic fatty liver disease was defined recently as another symptom of insulin resistance. Continuous therapy with valproate can result in increased body weight and insulin resistance, but no data are yet available on a possible relationship between valproate and nonalcoholic fatty liver disease. We here demonstrate in abdominal ultrasound investigations that characteristics of fatty liver disease were present in 61% of valproate‐treated patients as compared with 23% receiving carbamazepine therapy. Ann N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 73 publications
(72 reference statements)
6
74
0
Order By: Relevance
“…WhatsApp has been reported to be an effective and successful tool in the transfer of SP images in telepathology. [14][15][16] The present results showed that…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…WhatsApp has been reported to be an effective and successful tool in the transfer of SP images in telepathology. [14][15][16] The present results showed that…”
Section: Discussionmentioning
confidence: 69%
“…Because of these difficulties, TSI, RTIT, and WSI cannot be used in primary cytopathologic diagnosis, but they are used for secondary opinion, consultation, remote material adequacy assessment, training and examinations, and meetings. 2,4,[12][13][14] The recently developed microscopic imaging system with the highest technology is WSI.…”
mentioning
confidence: 99%
“…The availability of rose in interventional and endoscopy suites in Ontario is limited by human resource and financial constraints. Potential solutions to overcoming those barriers, which have had success in other jurisdictions, include expanding the role of cytotechnologists 51 and implementing tele-cytopathology assessment 52 . Additionally, direct and timely feedback from pathologists to clinicians about specimen adequacy and tumour cellularity for both core biopsy and cytology samples-for example, from endobronchial ultrasonography or bronchoscopy-can lead to continuous performance improvement.…”
Section: Solutions To Implementation Barriersmentioning
confidence: 99%
“…This distance can be across hospitals (allowing busy pathologists to avoid the time of travel necessary within institutions), from hospital to hospital within networks, from healthcare facilities to home after hours, or from anywhere in the world having a fast Internet connection. Studies have shown the utility of using telepathology in the real-time mode for rapid interpretations [9,10,11,12,13,14]. In one study using real-time dynamic telecytology to perform rapid assessments of pancreatic fine-needle aspiration biopsies, Kim et al [10 ]reported no significant disagreement between routine on-site and telecytology interpretations.…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%
“…Kerr et al [12] reported 97% concordance and 99% accuracy using a locally controlled real-time system for rapid assessment. Alsharif et al [13] reported only a 1.8% discrepancy rate using a real-time telecytology system, compared to a 3.1% discrepancy rate for routine glass-slide rapid evaluation, when each was compared to the final diagnosis. Their study was the largest to date, with over 400 cases analyzed.…”
Section: Telediagnosis/teleconsultationmentioning
confidence: 99%